Google Education for Distance Learning During the Covid 19 Pandemic - Safitri, Meilani; Aziz, M. Ridwan (International Conference on Elementary Education, 2022)
The COVID-19 pandemic has forced the government to make distance learning policies. Google Education is the platform that many educators choose to facilitate distance learning. This research is a qualitative descriptive study. The purpose of this study is to describe the implementation of google educatioan in distance learning in mathematics during the COVID-19 pandemic. The research subjects were 150 students of class X SMA Pradita Dirgantara. Data was collected through questionnaires and in-depth interviews. The data were analyzed with a qualitative approach. The results of this study, Google Education is effectively used in distance learning in mathematics during the COVID-19 pandemic